Is cash-return relation risk induced? - LIU, CHENXI (Institutional Knowledge at Singapore Management University, 2016)
Corporate cash holding is found to be able to predict stock return. Some scholars attribute this to the association of cash with systematic risk with respect to growth options. Others find that the relation is a mispricing effect. In this paper, I try to test whether the relation between cash and return is driven by systematic risk that captured by cash. The empirical results do not support the risk explanation of cash-return relation. First, the risk loading on CASH factor cannot predict returns, which is not consistent with rational frictionless asset pricing models. Second, CASH factor cannot reflect future GDP growth. Third, CASH and its factor loading exhibit no association with implied cost of capital derived from analysts’ earnings forecasts. Also, it is found that institutional investors tend to hold more shares of companies whose cash holdings intend to be high in the next period and the return spread by cash in firms with more institutional ownerships is lower than that in firms with less institutional ownerships. Overall, this paper casts doubt on the argument that cash can serve as a proxy of systematic risk in the explanation of cross sectional variation in stock returns, while it supports a mispricing explanation.